2021
DOI: 10.3390/nu13092964
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Vegetarian and Omnivorous Individuals: Analysis of 1340 Individuals

Abstract: The objective of this study was to evaluate the serum levels of ferritin and the prevalence of iron deficiency in vegan and omnivorous individuals by taking into account the presence of elements that cause an elevation of ferritin levels, such as increased homeostatic model assessment of insulin resistance (HOMA-IR), body mass index (BMI), and high-sensitivity C-reactive protein (hs-CRP) values. The parameters were evaluated in 1340 individuals, i.e., 422 men and 225 women who do not menstruate and 693 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
3
4
0
1
Order By: Relevance
“…Our group recently published data from the same sample presented in this article regarding iron metabolism, confirming the association between increased ferritin levels and IR and inflammation (assessed by hs-CRP dosage) [ 21 ]. Omnivorous individuals in our sample had significantly higher ferritin levels than vegetarians.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our group recently published data from the same sample presented in this article regarding iron metabolism, confirming the association between increased ferritin levels and IR and inflammation (assessed by hs-CRP dosage) [ 21 ]. Omnivorous individuals in our sample had significantly higher ferritin levels than vegetarians.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, in insulin resistance and increased systemic inflammation, there is an increase in ferritin levels, which acts as a marker of inflammation, and not of the body’s iron reserve, as demonstrated in a previously published study [ 21 ]. The increase in circulating concentrations of this acute phase protein is a predictor of the development of metabolic syndrome and NAFLD in adults [ 22 ].…”
Section: Introductionmentioning
confidence: 85%
“…A systematic review found that iron intake in vegan diets is higher than in non-vegans, but this is not always reflected in ferritin levels due to low bioavailability [185]. In the general population, women who do not menstruate and men have the same prevalence of iron deficiency when following an omnivorous or vegetarian diet [186]. An observational study evaluated lacto-ovo-vegetarian and omnivorous patients with CKD stage 3-5 and found no difference in haemoglobin levels between the two groups [187].…”
Section: Iron Deficiencymentioning
confidence: 99%
“…Sin embargo, existen otras investigaciones, como la de Nieman (1999), que afirman que las dietas vegetarianas pueden acarrear deficiencias nutricionales especialmente en nutrientes como hierro, calcio, fósforo, zinc y las vitaminas del complejo B. Para el caso del hierro (Fe), se ha demostrado que este mineral no es tan fácil de absorber por el organismo cuando su origen proviene de alimentos vegetales (hierro no hemo) en comparación al hierro que está en la carne y que es más fácil para el cuerpo su absorción y asimilación, este es un aspecto sumamente importante para el caso de las personas deportistas donde el hierro (Fe) juega un papel protagónico en la producción de hemoglobina, que a su vez transporta el oxígeno que necesita el organismo cuando hace ejercicio, la demanda de este micronutriente puede variar en la mujer en comparación al hombre debido a la menstruación por las pérdidas de sangre que se generan (Nieman, 1999). Pero, este no es un aspecto que deba preocupar, ya que la anemia no es común en personas vegetarianas (Slywitch et al, 2021) cuando llevan una alimentación variada y balanceada y además incluyen dentro de su alimentación algún suplemento dietario que pueda complementar las vitaminas y minerales que no consumen en su justa medida debido al régimen dietario a base de vegetales.…”
Section: Dieta Nutrición Y Saludunclassified